المؤشرات المالية ودورها في اتخاذ القرارات الإدارية دراسة ميدانية على شركة الخيوط القطنية في اللاذقية - نادر نهاد; الأمين ماهر; بزون حسين جواد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر دراسة المؤشرات المالية من أهم المواضيع التي يجب دراستها في أي شركة باعتبارها تقدم معلومات واسعة عن واقعها بحيث تبرز أهم نقاط القوة والضعف والتي من خلالها تسترشد إدارة الشركة وبالأخص المدير المالي بالمعلومات التي تقدمها والتي تعتبر مرتكزاً أساسياً لعملية اتخاذ القرارات لأن أي قرار يتخذ لا يعتمد على معلومات صحيحة سوف تكون نتائجه أخطر من عدم اتخاذه وقد تم هذا البحث على شركة الخيوط القطنية في اللاذقية من أجل تقديم دراسة شاملة تمكنها من معالجة مشاكلها وخاصة الخسائر المتتالية والتي ما زالت تلاحقها بالإضافة إلى إعادة هيكلة ديونها وبالأخص المطاليب المتداولة استناداً إلى هذه الدراسة. The financial ratios are the most important topics to be studied in any company, since they supply wide-ranging data about its actual situation, and it helps shed light on the most important points of weakness and strength, out of which the company management, and in particular the financial manager will obtain data considered essential in the process of taking decisions, since taking any decision not based on correct data will produce risky results. This study was done at the cotton yarn company in Lattakia, aiming to have a comprehensive study enabling it to deal with its problems, particularly the sequential losses still affecting it, in addition to reorganizing its debts, the most important of which being current liabilities based on this study.